Inequalities in the Employment of Municipality Law Enforcement Staff - Békési, László (Magyar Rendészet, 2017)
In meeting their law enforcement tasks, municipalities may engage persons in assistant community support officer positions as employees either employed directly by themselves or, in special cases, in the framework of temporary agency work. However, as far as the requirements of equal treatment are concerned, the joint application of the two types of employment highlights problematic situations which may also occur in other fields of temporary agency work. The purpose of this study is to reveal such problems, inequalities, and to provide suggestions regarding the elimination thereof, with due consideration of EU directives.